1995
DOI: 10.1080/07399339509516197
|View full text |Cite
|
Sign up to set email alerts
|

The impact of marital status and quality on family functioning in maternal chronic illness

Abstract: Married individuals tend to enjoy greater health and well-being than nonmarried. However, investigators disagree about whether this is related to the quality of the marriage or to participation in the socially accepted role of marriage. In the present study, we examined the roles of marital quality and marital status as predictors of the family's adjustment processes in the context of maternal chronic illness. We found that the family functioning of single women and unhappily married women was similar and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Though interventions designed to improve family relationship quality could impact breast cancer outcomes, women whose family relationships are of poor quality may also benefit from extrafamilial relationships. Poor quality family relationships may be related to poorer health outcomes[32, 33], and religious and community participation has generally been related to better health outcomes[34] and lower mortality[3537]. …”
Section: Discussionmentioning
confidence: 99%
“…Though interventions designed to improve family relationship quality could impact breast cancer outcomes, women whose family relationships are of poor quality may also benefit from extrafamilial relationships. Poor quality family relationships may be related to poorer health outcomes[32, 33], and religious and community participation has generally been related to better health outcomes[34] and lower mortality[3537]. …”
Section: Discussionmentioning
confidence: 99%
“…A greater number of studies have assessed aspects of family functioning, such as cohesion and conflict. In a series of interrelated studies of the families of women with either breast cancer, fibrocystic breast disease, or diabetes, family functioning was measured using self-report scales assessing family adaptability, cohesion, and/or the family's satisfaction with the quality of the family's interactions (Lewis et al, 1989(Lewis et al, , 1993Yates et al, 1995). These measures of family functioning were modestly related to illness severity, with some families at risk for low cohesion and increased conflict when the illness was more severe.…”
Section: Association Between Parental Illness and Family Functioningmentioning
confidence: 99%
“…The ill parent's gender has seldom been studied as a moderator. Most studies sample ill parents of only one gender-usually mothers (e.g., Dura & Beck, 1988;Lewis et al, 1989Lewis et al, , 1993Yates et al, 1995). One study of cancer patients and their spouses (Compas et al, 1994) revealed that the perceived seriousness of the illness varied by the adult's gender and status as patient or (healthy) spouse: Women perceived the cancer as more stressful than men, as did spouses (vs. patients).…”
Section: Ill Parent's Gender or Family Rolementioning
confidence: 99%
See 1 more Smart Citation
“…Demographic factors may also influence perceptions of family functioning. Age, marital status, and gender have previously been associated with perceived family functioning and wellbeing, albeit inconsistently, when a family member is diagnosed with cancer [17][18][19]. For example, a metaanalytic study found that mothers of children with cancer reported higher family conflict than controls, but this difference was not found for fathers [20].…”
Section: Discussionmentioning
confidence: 99%